Anàlisi contrastiva dels marcadors de reformulació i exemplificació - Cuenca, Maria Josep (Caplletra. Revista Internacional de Filologia, 2001)
The aim of this paper is to present a contrastive analysis of reformulation and exemplification markers in Catalan and Spanish,on the one hand, and in English, on the other. The study is based on a corpus of expository prose (mainly academic writing). The analysis shows coincidences regarding the sources of the connectives, but also differences relating to the variety of forms and the preference of fixed or variable connectives. The differences identified in the grammar of Catalan and Spanish vs. that of English will be associated with two distinct styles for building expository texts.